A multiplex PCR system for detection of wide compatibility allele S5-n and erect panicle allele dep1 in rice - Li,Jun Zhou (2017)
Abstract Wide compatibility and erect panicles are important traits for heterosis and ideal plant type breeding in rice and accordingly are targets for rice yield improvement. In this study, a multiplex PCR system based on functional markers was developed to simultaneously identify genotypes of the wide compatibility allele S5-n and the erect panicle allele dep1. Forty-nine rice varieties in the Huang-Huai-Hai region of China were identified using this system. Thirty-three varieties contained the erect panicle allele dep1 and two varieties contained the wide compatibility allele S5-n. The frequency of dep1 was obviously higher than that of S5-n. The multiplex PCR method was also tested using an F2 segregating population and was found to be simple, efficient, and reliable. It will be useful in marker-assisted selection based on the wide compatibility allele S5-n and erect panicle allele dep1 to breed super rice varieties using indica and japonica heterosis.